Occurrence of mycotoxins in milk thistle: to be included in legislation or not? - Boško, Rastislav; Pluháčková, Helena; Martiník, Jan; Benešová, Karolína; Svoboda, Zdeněk; Běláková, Sylvie; Pernica, Marek (Mycotoxin research, 2025)
The silymarin complex extracted from milk thistle provides significant health benefits, particularly due to its antioxidant and hepatoprotective properties. However, plant substances can be contaminated by a number of fungi types and their secondary metabolites-mycotoxins. This work deals with the determination of aflatoxins and zearalenone and its metabolites in 39 different samples grown in 2020 and 2021. Analysis of mycotoxins was performed by UHPLC-MS/MS after immunoaffinity column AFLAPREP® and EASI-EXTRACT® ZEARALENONE clean-up. The presence of aflatoxins was not confirmed in the monitored samples, but 1/3 of the samples were contaminated with zearalenone in the range of 2.8-378.9 µg/kg. Metabolites of zearalenone such as α-zearalenol, α-zearalanol, and β-zearalanol were not detected in any of the samples. β-Zearalenol was found in two samples (2.6 µg/kg and 29.8 µg/kg).
Keywords: kontaminace potravin; Mycotoxins; mykotoxiny; Food safety; tandemová hmotnostní spektrometrie; Silybum marianum; UHPLC-MS/MS; Chromatography, High Pressure Liquid; Zearalenone; aflatoxiny; Aflatoxins; Tandem Mass Spectrometry; Food Contamination; ostropestřec mariánský; vysokoúčinná kapalinová chromatografie; Milk thistle; zearalenon